Platelet components associated with adverse reactions: predictive value of mitochondrial DNA relative to biological response modifiers. Issue 2 (7th October 2015) - Cognasse, Fabrice; Aloui, Chaker; Anh Nguyen, Kim; Hamzeh‐Cognasse, Hind; Fagan, Jocelyne; Arthaud, Charles‐Antoine; Eyraud, Marie‐Ange; Sebban, Marc; Fromont, Elisa; Pozzetto, Bruno; Laradi, Sandrine; Garraud, Olivier
Abstract : BACKGROUND: Biological response modifiers (BRMs), secreted by platelets (PLTs) during storage, play a role in adverse events (AEs) associated with transfusion. Moreover, mitochondrial DNA (mtDNA) levels in PLT components (PCs) are associated with AEs. In this study we explore whether there is a correlation between pathogenic BRMs and mtDNA levels and whether these markers can be considered predictors of transfusion pathology. STUDY DESIGN AND METHODS: We investigated a series of reported AEs after PC transfusion, combining clinical observations and mathematical modeling systems. RESULTS: mtDNA was consistently released during the first days of PC storage; however, mtDNA release was earlier in "pathogenic" than in nonpathogenic PCs. PC supernatants with high levels of mtDNA along with soluble CD40 ligand (sCD40L) were significantly associated with occurrences of AEs. The fact that mtDNA did not associate with the 14 BRMs tested suggests the role of mtDNA in PC transfusion‐linked inflammation is independent of that of BRMs, known to be associated with AEs. We present evidence that PLTs generate distinct pathogenic secretion profiles of BRMs and mtDNA. The calculated area under the curve for mtDNA was significantly associated with AEs, although less stringently predictive than those of sCD40L or interleukin‐13, standard predictors of AE. The established model predicts that distinct subtypes of AEs can be distinguished, dependent on mtDNA levels and PC storage length. CONCLUSIONS: Further work should be considered to test the propensity of mtDNA in PLT concentrates to generate inflammation and cause an AE.